Comparison of different culture media for mycological evaluation of commercial pet food - Marina Venturini Copetti (Acta Scientiae Veterinariae, 2009)
The choice of a culture media to proceed a mycological analysis of food is extremely important to guarantee the reliability of the analysis. The medium should allow an excellent recovery of fungal species present in the food at the same time that it is necessary to avoid bacterial development. Thus the real microbial ecology will be reflected in the results. The efficacy of three media for fungal isolation and quantification (potato dextrose agar, dichloran rose of bengal and chloramphenicol agar and dichloran glycerol 18% agar) was compared for analysis of 54 samples of dry commercial pet food (34 for dogs and 20 for cats). Fungi were present in 74% of samples and 23 genera were isolated and identified. Aspergillus sp. and Aspergillus niger were respectively the most frequent genera and species isolated, whatever the culture medium selected to proceed the analysis. Dichloran glycerol 18% agar was the medium that presented the best results considering both the quantity and variety of isolated fungi. Comparing the results obtained in different media, it was observed that the fungi recovered can vary according to the selected culture medium. Eurotium was the genus that presented the biggest difference in occurrence among the media where samples were cultivated to enumeration in this study. Therefore, the utilization of specific media, selected according to the characteristics of the food to be analyzed (specially water activity) allow a better visualization of the presence of food spoilage fungi.